The Role of Interpersonal Communication and Work Motivation in Improving Employee Work Performance at PT PLN (PERSERO) UIP3BS UPT MEDAN - Evo Marisi Tumpal Damanik; Tonggo Sangap Timbul Girsang; Mery Suliyanti H. Sitanggang; Melky F. Simatupang (Universitas Dehasen Bengkulu, 2025)
This study, titled